The European Seaborne Empires : From the Thirty Years' War to the Age of Revolutions - Paquette, Gabriel B. (Yale University Press, 2019)
In this thematic survey, Gabriel Paquette focuses on the development of the Spanish, Portuguese, English, French, and Dutch overseas empires in the seventeenth and eighteenth centuries. He draws on recent advances in the field to re-examine their development, from efficacious forms of governance and finance to coercive violence. Beginning with a narrative overview of imperial expansion that incorporates recent critiques of older scholarly approaches, Paquette then analyzes the significance of these empires, including their political, economic, and social consequences and legacies. He makes the multifaceted history of Europe's globe-spanning empires in this crucial period accessible to new readers.